Attitudes towards induced abortion among gynecologists in Kurdistan region of Iraq - Gashaw Khalid; Abubakir Majeed Saleh; Nazar Shabila; Malin Bogren; Delér Shakely (BMC, 2023)
Abstract Background Unsafe abortion is a major contributor to maternal morbidity and mortality in countries where induced abortion is restricted. In Kurdistan Region of Iraq, induced abortion is strictly forbidden except for life-threatening situations, increasing the risk of seeking unsafe abortions. Attitudes among healthcare professionals who directly encounter cases and consequences of induced abortion can be studied to improve women's access to safe abortion. This study aimed to examine attitudes towards induced abortion among gynecologists in Kurdistan Region of Iraq. Methods This cross-sectional facility-based study was conducted in the first quarter of 2022 in Kurdistan Region of Iraq in the cities of Erbil, Sulaymaniyah, and Duhok. Convenient sampling was used to invite 330 gynecologists to participate, with 171 ultimately completing the questionnaire, giving a response rate of 53%. Questionaries using the Taylor and Whitehead abortion attitude scale were sent in person or digitally. The data was then analyzed using Chi-square and Fisher's exact tests to determine the independence of attitudes and associations between attitudes and sociodemographic factors. Results Among 171 gynecologists, 25% of the gynecologists agreed that induced abortion is unacceptable under any circumstances. Most (71%) disagreed that a woman has the right to choose to have an induced abortion. Around 51% considered induced abortion murder, and 41% agreed that induced abortion goes against all morals. Around 57% disagreed with the legalization of induced abortion, while 43% agreed. Gynecologists who were unmarried (P = 0.025), under the age of 40 (P = 0.044), and with less than 10 years of clinical experience (P = 0.043) were more likely to support the legalization of induced abortion in Kurdistan Region. None of the variables was found to be independently associated with attitudes towards abortion legalization. Conclusions Despite some younger gynecologists having more favorable attitudes towards induced abortion, most gynecologists in Kurdistan Region had less favorable views. Most gynecologists were willing to provide post-abortion care regardless of their legal status. We recommend conducting more studies to investigate the consequences of current abortion legislation among women in need of induced abortion in Kurdistan Region of Iraq.